Death anxiety in oncological disease - Segovia Cereceda, Sofía; Acuña Acuña, Bruno; Muñoz Garrido, Andrea; Becerra López, Nataly; Campusano Villablanca, Daniela; Cantin Alfaro, Sebastián (Revista Chilena de Estudiantes de Medicina, 2024)
Death anxiety is a common and significant phenomenon among patients with oncological diseases, but it lacks a distinct diagnosis in International Disease Classifications. The absence of appropriate treatment can adversely impact prognosis, therapeutic adherence, and quality of life. While there is limited evidence concerning the pharmacological treatment of death anxiety, non-pharmacological management is emphasized. This includes meaning-based interventions, which help patients cope with existential issues and loss, and dignity-focused interventions, which promote reflection on life conflicts. In Chile, despite legislative advances, a multidisciplinary approach and the implementation of specific protocols in the field of palliative care are needed to address this issue adequately.